Application of International Private Law Doctrines to Cross-Border “Green” Agreements (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
In the context of the global transition to sustainable development, the importance of cross-border agreements aimed at environmental protection is increasing. This article is dedicated to the analysis of key doctrines of private international law applied within the framework of “green” cross-border transactions, including the autonomy of the parties’ will, the principle of closest connection, imperative norms, and public policy. Legal approaches of various countries are examined, and the problems and prospects of legal regulation from the perspective of sustainable development are outlined.